Can ESG Performance Moderate The Effect of Tax Avoidance on Corporate Risk? - Verani Carolina; Yuliana Gunawan; Ranesa Tedya (Universitas Muhammadiyah Surakarta, 2023)
Very few companies in Indonesia implement environmental, social, and governance (ESG), but nowadays investors are interested in investing in companies that have good ESG profiles. This study aims to find the moderating effect of ESG performance on the effect of tax avoidance on corporate risk. The ESG score was obtained through the Thomson Reuters Eikon (Refinitiv), while tax avoidance was measured using the Effective Tax Rate and Cash Effective Tax Rate. This study used a sample of companies with ESG scores in the 2012-2021 period. The data was analyzed using panel data moderation regression with eviews 12. The best regression model obtained is the Fixed Effect Model (FEM). The results showed that ESG performance can moderate the effect of tax avoidance on corporate risk.Keywords: Environmental, Social, and Governance (ESG), tax avoidance, corporate risk.